Accounting for intergenerational social immobility in low- and middle-income countries - Fabian Koenings; Jakob Schwab (Friedrich Schiller University Jena, 2020)
This study investigates the transmission channels of intergenerational social immobility in low- and middle-income countries. Using a rich longitudinal survey dataset on Ethiopia, India, Peru, and Vietnam, we analyze through which factors socioeconomic status is passed on between generations. We reduce the information elicited throughout children's youth to certain latent factors of their development process, such as cognitive and non-cognitive skills as well as the characteristics of their social environment and the social opportunities they face. We then analyze to what extent each of these factors is explained by parental socioeconomic status, and how much each factor in turn determines the outcome of the children. Next, we combine these results in order to decompose the immobility into the different pathway factors. The findings indicate that children's aspirations and their cognitive skills can each account for around 20 percent of the correlation between parental and children's education. Starting a family while still a minor, and the need for child labor also play important, but smaller roles, explaining 10 percent and 6 percent of the immobility, respectively. While children's health, parent's attentiveness and the local school infrastructure only have small but still significant roles, parents' spending on education, children's social environment, and particularly children's non-cognitive skills have no significant part in the transmission of socioeconomic status in the sample of developing countries, once all other factors are taken into account.
Keywords: I24; J62; O15; 330; Intergenerational social mobility; transmission mechanisms; low- and middle income countries